Proton therapy for pediatric head and neck malignancies. Issue 2 (23rd October 2017) - Vogel, Jennifer; Both, Stefan; Kirk, Maura; Chao, Hann‐Hsiang; Bagatell, Rochelle; Li, Yimei; Womer, Richard; Balamuth, Naomi; Reilly, Anne; Kurtz, Goldie; Lustig, Robert; Tochner, Zelig; et al.
Abstract: Purpose: Pediatric head and neck malignancies are managed with intensive multimodality therapy. Proton beam therapy (PBT) may reduce toxicity by limiting exposure of normal tissue to radiation. In this study, we report acute toxicities and early outcomes following PBT for pediatric head and neck malignancies. Materials and methods: Between 2010 and 2016, pediatric patients with nonhematologic malignancies of the head and neck were treated with PBT. Clinical and dosimetric data were abstracted from the medical record and treatment planning system with institutional review board approval. Results: Sixty‐nine consecutive pediatric patients were treated with proton‐based radiotherapy for head and neck malignancies. Thirty‐five were treated for rhabdomyosarcoma to a median dose of 50.4 Gy relative biological effectiveness [RBE]. Ten patients were treated for Ewing sarcoma to a median dose of 55.8 Gy[RBE]. Twenty‐four patients were treated for other histologies to a median dose of 63.0 Gy[RBE]. Grade 3 oral mucositis, anorexia, and dysphagia were reported to be 4, 22, and 7%, respectively. Actuarial 1‐year freedom from local recurrence was 92% (95% CI 80–97). Actuarial 1‐year overall survival was 93% (95% CI 79–98) in the entire cohort. Oral cavity mucositis was significantly correlated with oral cavity dose (D80 and D50 [ P < 0.05], where D80 and D50 are dose to 50% of the volume and dose to 80% of the volume, respectively). Conclusions: In this study, we report low rates of acute toxicity in a cohort of pediatric patients with head and neck malignancies. PBT appears safe for this patient population, with local control rates similar to historical reports. Longer follow‐up will be required to evaluate late toxicity and long‐term disease control.